Medio-lateral knee fluency in anterior cruciate ligament-injured athletes during dynamic movement trials - Panos, J. A.; Hoffman, J. T.; Wordeman, S. C.; Hewett, T. E. (Clinical Biomechanics, 2016)
Correction of neuromuscular impairments after anterior cruciate ligament injury is vital to successful return to sport. Frontal plane knee control during landing is a common measure of lower-extremity neuromuscular control and asymmetries in neuromuscular control of the knee can predispose injured athletes to additional injury and associated morbidities. Therefore, this study investigated the effects of anterior cruciate ligament injury on knee biomechanics during landing.